2011
DOI: 10.1111/j.1365-2605.2011.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

The mode of reproductive‐derived Spink (serine protease inhibitor Kazal‐type) action in the modulation of mammalian sperm activity

Abstract: Summary The reproductive‐derived serine protease inhibitor Kazal‐type (Spink) has been identified in seminal plasma, and Spink–spermatozoa binding has been illustrated in many mammalian species including human. We used mice as experimental animal to study the mode of Spink action in the modulation of mammalian sperm activity. A Spink3‐binding zone was cytochemically stained on the sperm head at apical hook separated from intact acrosome, whether the cells were capacitated or not. The Spink3–spermatozoa binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
(48 reference statements)
5
18
0
Order By: Relevance
“…In agreement with previous results of purified caltrin I from rat (Dematteis et al 2008) and recombinant SPINK3 (Ou et al 2012), we observed an inhibition of both spontaneous and P 4 -induced AR mediated by GST-SPINK3, while viability remained invariable. However, the physiological significance of the effect over induced AR is uncertain.…”
Section: G S T -S P I N K 3 + S N P G S T -S P I N K 3 + G S N O G S supporting
confidence: 81%
See 4 more Smart Citations
“…In agreement with previous results of purified caltrin I from rat (Dematteis et al 2008) and recombinant SPINK3 (Ou et al 2012), we observed an inhibition of both spontaneous and P 4 -induced AR mediated by GST-SPINK3, while viability remained invariable. However, the physiological significance of the effect over induced AR is uncertain.…”
Section: G S T -S P I N K 3 + S N P G S T -S P I N K 3 + G S N O G S supporting
confidence: 81%
“…Accordingly, in this work we showed that a modified recombinant SPINK3 protein that lacks trypsin inhibitory activity (GST-SPINK3) can bind sperm, reduce intracellular Ca 2C concentration, and modulate AR and protein phosphorylation, while it has no effect on sperm motility. All these data taken together show that the serine protease inhibitory activity of SPINK3 might not be necessary in sperm signaling which is consistent with the results obtained by Ou et al (2012) with the recombinant SPINK3 carrying the point mutation R19L.…”
Section: Spink3 Involves No Signalling In Spermsupporting
confidence: 79%
See 3 more Smart Citations